Dentists' knowledge, attitude, and practice regarding evidence-based practice in Davangere, India - Purvi Mahesh Bhate; Sakeenabi Basha; Prashant Manjunath Goudar; Sushanth V Hirekalmath; Imranulla Mohamed; C R Allama Prabhu (Wolters Kluwer Medknow Publications, 2017)
Introduction: Evidence-based practice (EBP) is a widely accepted term in the medical field around the world. EBP means integrating individual clinical expertise with the best available external clinical evidence from systematic research, thus integrating and ensuring that the right treatment is given to the patient. Aim: This study aims to assess the existing level of knowledge, attitude, and practice regarding EBP among dentists in Davangere city, Karnataka, India. Materials and Methods: A cross-sectional questionnaire survey was conducted among 160 dentists in Davangere city. Pretested questionnaire was distributed to them, of which 117 responded. Descriptive statistics was applied. Results: The response rate was 73.12% (117); among the respondents, 94.8% (111) were aware of EBP and 77% (97) had come across the word at conferences/continuing dental education programmers. When faced with clinical uncertainty, 37% (53) dentists used electronic source with regard to EBP and only 38.5% (45) were aware of evidence-based pyramid. Conclusion: Most of the respondents were aware of the term EBP; however, the level of knowledge is limited. Dentists require adequate training to enable them to practice efficient EBP.